Lewis acid catalyzed cascade annulation of alkynols with alpha-ketoesters: a facile access to gamma-spiroketal-gamma-lactones - Kambale, Digambar A.; Thorat, Sagar S.; Pratapure, Madhukar S.; Gonnade, Rajesh G.; Kontham, Ravindar (Chemical Communications, 2017)
A novel Lewis acid catalyzed intermolecular cascade annulation of alkynols with alpha-ketoesters has been developed. This simple and efficient cascade annulation proceeds through a 5-exo-dig cyclization of alkynols followed by annulation with alpha-ketoester to provide a wide variety of unsaturated gamma-spiroketal-gamma-lactones (1,6-dioxaspiro[4.4]non-3-en-2-ones) related to many natural products.

Bismuth(III)-catalyzed cycloisomerization and (hetero)arylation of alkynols: simple access to 2-(hetero)aryl tetrahydrofurans and tetrahydropyrans - Nakate, Ashwini K.; Pratapure, Madhukar S.; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2018)
2-(Hetero)aryl tetrahydrofurans and tetrahydropyrans were successfully synthesized using Bi(OTf)(3)-catalyzed hydroalkoxylation (cycloisomerization) of alkynols (via 5 or 6 exo-dig cyclization) and intermolecular (hetero)arylation. This reaction involves a highly efficient cascade process, where initially the alkynol undergoes a cycloisomerization step via activation of the triple bond and generates the oxocarbenium ion, which subsequently participates in the (hetero)hydroarylation step with electron-rich arenes. Simple to complex suitably functionalized alkynols (4-pentyn-1-ols and 5-hexyn-1-ols) and electron-rich aromatic compounds were found to be reliable substrates in this cascade transformation and furnished a wide range of oxygen heterocycles. This practical tandem process provides a means to build libraries related to pharmacologically active molecules and natural product like scaffolds.

Studies directed toward the total synthesis of nannocystin A - Nomula, Rajesh; Pratapure, Madhukar S.; Kontham, Ravindar (ChemistrySelect, 2022)
A full account of our efforts directed toward the stereoselective total synthesis of nannocystin A, a macrocyclic myxobacterial metabolite, is presented. In this endeavor, we have attempted two distinct synthetic routes to access polyketide fragment (C1-C11) of macrocyclic depsipeptide (21-membered) natural product from readily accessible building blocks 1,3-propanediol and benzaldehyde employing Evans aldol, CBS reduction, Heck cross-coupling, and Sharpless asymmetric epoxidation as key transformations. Ultimately, accomplished the synthesis of the complete skeleton (21-membered precursor for macrocyclic depsipeptide) of the nannocystin A possessing desired stereochemistry and functional groups.
Keywords: amidation; Depsipeptide; Evans aldol reaction; Macrocycle; Nannocystins

Bismuth(III)-catalyzed cascade condensation of alkynyl alcohols with terminal alkynes: a facile construction of propargyl cyclic ethers - Pratapure, Madhukar S.; Kontham, Ravindar (Tetrahedron Letters, 2023)
Herein, we report a Bi(OTf)3-catalyzed cascade condensation between alkynols (particularly pent-4-yn-1ols and hex-5-yn-1-ols) and terminal alkynes (aryl alkynes) to facile access to diverse propargyl cyclic ethers (2 alkynyl tetrahydrofurans and 2 alkynyl tetrahydropyrans). This simple and efficient cascade transformation proceeds through initial intramolecular hydroalkoxylation of alkynols to give corresponding cyclic enol ethers (via exo-dig or endo-dig mode of ring-closure) followed by hydroalkynylation. Costeffective, naturally abundant, green Lewis acid catalysis, ambient reaction conditions, short reaction times, good substrate scope, and high yields are salient features of this strategy.(c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Alkynyl alcohols; Bismuth catalysis; Cascade condensation; Propargyl cyclic ethers; Terminal alkynes